Aggressiveness of ganoderma boninense isolates On the vegetative growth of oil palm (Elaeis guineensis) seedlings at different ages - Goh, Y.K.; Ng, F.W.; Kok, S.M.; Goh, Y.K.; Goh, K.J. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Basal stem rot (BSR) disease caused by Ganoderma boninense is rapidly spreading in both coastal and inland soils planted with oil palms (Elaeis guineensis) across Indonesia and Malaysia. A study was conducted to evaluate the effects of different G. boninense isolates collected from different regions of Peninsular Malaysia on oil palm seedlings. Ganoderma boninense isolates from 12 different estates located in 7 states were collected and used for assessing the effects of pathogenic Ganoderma isolates on 2- and 5-month-old oil palm seedlings. These seedlings were challenged artificially with Ganoderma-inoculated rubber wood blocks as the inoculum source. Based on the disease severity index (DSI), G. boninense isolates from Bt Lintang (Kedah) (T10) (63.3%) were the most aggressive, whereas, Fraser (Johor) (T4) (8.3%) and Pinji (Perak) (T8) (3.7%) were the least aggressive. Vegetative growth measurements (VGM), namely leaf area (cm2), diameter of the bole girth (cm) and height (cm), for both 2- and 5-month-old seedlings challenged with the most aggressive T10 isolate were significantly lower compared to both of the least aggressive isolates – T4 and T8, as well as the controls at 4 months-after-treatment (MAT). The linear correlation between DSI with VGM at 16-weeks after treatment was negative, ranging from 0.64 to 0.88 for 5-month-old seedlings. Two-month-old seedlings are more preferable in the future nursery experiments compared to 5- month-old seedlings, as the former seedlings were more responsive in terms of DSI and all the VGM parameters measured.